El pensamiento económico de Nicolás Avellaneda en torno al empréstito extranjero - Cuccorese, Horacio J. (1957)
Nicolás Avellaneda, professor of Economics at the University of Buenos Aires, when only 23 years old, was as intelligent representative of the classical school. He exposes his principles with a personal flavour and admirable eloquence. When 28 years old he wrote his "Estudios sobre las Leyes de Tierras Públicas", a master work of Argentine economic historiography. His conceptions of foreign loans can be resumed as follows: 1º He was not against foreign loans but, in order to avoid risks and sacrifices, he advises to appeal first to the nation's possibilities; 2º A loan is paid back by taxes and is detrimental to futures generations; 3º The future cannot be foreseen; the Argentine historical experience has shown, especially whit regard to the first British loan, that the works contemplated were never executed, aggravating thus the economic situation; 4º Only in case of extreme necessity could a foreign loan be justified, but the interested country cannot count upon the capitalist's generosity. This is why a foreign loan should be prudently negotiated. Neither the present economic principles, nor the jurisprudence are contradicting Avellanedas's ideological position and we have to admit that his work are of a high value for the economic culture of Argentina